Avaliação de um programa de comunicação alternativa e ampliada para mães de adolescentes com autismo - Walter, Catia Crivelenti de Figueiredo (2006)
Considering the communication deficit and the behavior desorder as a symptom present in autism, it would be logic to rationalize that these factors are all interconnected. The literature has been showing that families, that have a familiar with autism, have difficulties using the methods of Alternative and Augmentative Communication (AAC) with people with severe communication deficit. Therefore, the objective of this study was to apply and to analyze the effect of an AAC program in the context of a family that has a member with autism. The program named ProCAAF, was applied according to the real necessities of the families to establish an effective communication among their children according to the necessities presente in the family context. The study analyzed the effects of the the AAC application and recorded the communication behavior changes within family members and their children. There were 3 participants in this study: (Pfs), representing mothers and their respective children. (Pas), representing students diagnosed with autism with no verbal communication or functional speech. A multiple probe design accross the Pfs and Pas was employed to verify the the effects of the ProCAAF program and envolved two phases: baseline and intervention. The Pfs performance in the application of the AAC in the family context, was the independent variable of the study and the Pas performance in the utilization of CAA in the family context was the dependent variable. The quantitative data was analyzed through the level of support received from the Pfs during the application of the AAC offered by the researcher and by the performance of the Pfs soliciting their needs and desires utilizing the AAC. The results showed that the Pfs learned how to apply the AAC in the family context and achieved the communication priorities determined previously. Furthermore, significant changes in the communication behavior from the Pas occurred in relation to the request of the items non-present inside the houses and the expression of their feelings such as: pain and homesickness. The qualitative data was analyzed from the answers, which were obtained from a questionnaire applied pre and pos intervention period indicating significant change in relation to the communication ability of the Pas, such as: a reduction of the non desired behavior, clarity in communicative situations, increases in the communicative act. One of the Pas, was able to emit words with communicative function. The study concluded that the use of AAC in a family context corroborated to the benefits in the interpersonal relation with people with autism and it suggested new research and extension of the program in a different context.